Resin composition and foam

JP7634429B2Active Publication Date: 2025-02-21INOAC TECHN CENT
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021088014
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-06-30
Filing Date
2021-05-25
Publication Date
2025-02-21
Estimated Expiration
2041-05-25

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、難燃材としての基本特性(難燃性、形状保持性等)を担保しつつ、劣悪な環境下(特に、高温高湿下)でも圧縮強度が劣化し辛い発泡体及びその原料である樹脂組成物を提供することが可能となる。更に、本発明によれば、難燃性を担保しつつ、延焼の進行が抑制可能な発泡体及びその原料である樹脂組成物を提供することが可能となる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007634429000013
    Figure 0007634429000013
  • Figure 0007634429000001
    Figure 0007634429000001
  • Figure 0007634429000002
    Figure 0007634429000002
Patent Text Reader

Abstract

To provide: a foam whose compressive strength hardly deteriorates even under poor environments (particularly under high humidity and high temperature) while securing basic characteristics as a flame retardant, such as flame retardancy and shape retention; and a resin composition as an ingredient thereof.SOLUTION: The resin composition comprises: a resin component comprising an isocyanate terminated prepolymer having at least 2 or more isocyanate groups, obtained from a polyisocyanate and a compound having 2 or more active hydrogen atoms; a polyamine; a trimerization catalyst; a flame retardant; a foaming agent; and a foam stabilizer.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition and a foam. [Background technology]

[0002] Urethane foam is used for construction purposes, ships for transporting oil and gas, and as a heat retaining and insulating material for electrical appliances such as refrigerators. In particular, in buildings made of reinforced concrete, the spraying method of applying urethane foam is used because it is easy to apply insulation. The spraying method is a method in which the undiluted urethane foam is sprayed onto the building frame using a spraying device, and simultaneously foamed to form a urethane foam insulation structure.

[0003] In general, polyurethane resins are characterized by excellent elasticity, flexibility, and tensile strength, as well as excellent abrasion resistance and impact strength. However, urethane foam alone is highly flammable, so studies have been conducted to improve the flame retardancy of urethane foam.

[0004] As such a urethane foam, Patent Document 1 discloses a composition for forming a water-foamed rigid polyisocyanurate foam, which comprises an organic polyphenylmethane polyisocyanate, a polyol, a trimerization catalyst, water as a blowing agent, a foam stabilizer, and a flame retardant. The invention of Patent Document 1 is characterized in that the polyol contains a chlorinated polyether polyol having a primary and / or secondary hydroxyl group, which is obtained by using an active hydrogen-containing compound as a polymerization initiator and performing ring-opening polymerization of a chlorinated epoxy compound in the presence of an acid catalyst, and that the organic polyphenylmethane polyisocyanate and the polyol are blended so that the isocyanate index is 120 to 400. It has been shown that the urethane foam using the composition for forming a water-foamed rigid polyisocyanurate foam of Patent Document 1 is excellent in the working environment and has excellent flame retardancy.

[0005] Patent Document 2 discloses a flame-retardant urethane resin composition comprising polyisocyanate, polyol, trimerization catalyst, blowing agent, foam stabilizer and additive, the trimerization catalyst being at least one selected from the group consisting of nitrogen-containing aromatic compounds, alkali metal carboxylates, tertiary ammonium salts and quaternary ammonium salts, the additive containing red phosphorus as an essential component and at least one selected from the group consisting of phosphoric acid esters, phosphate-containing flame retardants, bromine-containing flame retardants, boron-containing flame retardants, antimony-containing flame retardants and metal hydroxides in combination with red phosphorus. It is shown that a urethane foam using the flame-retardant urethane resin composition of Patent Document 2 is easy to handle, has excellent flame retardancy and can form a foam that maintains a certain shape when heated. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2013-023510 A [Patent Document 2] JP 2017-075326 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]

[0007] Here, it is preferable that the physical properties of the flame retardant do not change over time even under poor environments (particularly under high temperature and high humidity). In particular, the present inventors have found that the flame retardant effect decreases over time when the compressive strength deteriorates. Therefore, the main object of the present invention is to provide a foam and a resin composition as a raw material thereof, which are difficult to deteriorate in compressive strength even under poor environments (particularly under high temperature and high humidity) while ensuring basic properties as a flame retardant (flame retardancy, shape retention, etc.). In addition, it is preferable that the flame retardant is not only flame retardant but also a material that is difficult to spread fire even if a fire occurs. While the present inventors have been conducting verification from this perspective, they have confirmed that although conventional urethane foams have excellent flame retardancy, the spread of fire is unexpectedly likely to progress. Therefore, the secondary object of the present invention is to provide a foam and a resin composition as a raw material thereof, which are capable of suppressing the spread of fire while ensuring flame retardancy. [Means for solving the problem]

[0008] The present invention (1) is a resin composition comprising: a resin component containing an isocyanate-terminated prepolymer having at least two isocyanate groups, the prepolymer being obtained by reacting a compound having two or more active hydrogens with a polyisocyanate; a polyamine; a trimerization catalyst; a flame retardant; a foaming agent; and a foam stabilizer. The present invention (2) relates to the resin composition according to the invention (1), wherein the viscosity of the resin component at 25° C. is 100 to 7,000 mPa·s. The present invention (3) relates to the resin composition according to the invention (1) or (2), wherein the blending amount of the polyamine is 0.1 to 30 mass % based on the total mass of the resin components. The present invention (4) is the resin composition according to any one of the above inventions (1) to (3), wherein the NCO% in the resin component is 10 to 35% by mass. The present invention (5) is the resin composition according to any one of the inventions (1) to (4), wherein the resin composition further contains a polyisocyanate different from the isocyanate-terminated prepolymer. The present invention (6) is the resin composition according to any one of the above-mentioned inventions (1) to (5), wherein the compound having two or more active hydrogens is at least one selected from the group consisting of polyols, polyamines, and polythiols. The present invention (7) is the resin composition according to any one of the above inventions (1) to (6), wherein the trimerization catalyst is an organometallic salt, a quaternary ammonium salt, or a nitrogen-containing heterocyclic compound. The present invention (8) relates to the resin composition according to any one of the inventions (1) to (7), which further contains red phosphorus. The present invention (9) relates to the resin composition according to the invention (8), further comprising at least one flame retardant selected from the group consisting of phosphoric esters, phosphate-containing flame retardants, bromine-containing flame retardants, boron-containing flame retardants, antimony-containing flame retardants, and metal hydroxides. The present invention (10) is a foam obtained from the resin composition of any one of the above inventions (1) to (9). The present invention (11) relates to the foam according to the invention (10), wherein the foam has an isocyanurate ratio of 20% or more and 50% or less. Effect of the Invention

[0009] According to the present invention, it is possible to provide a foam that is resistant to deterioration in compressive strength even under adverse environments (particularly under high temperature and high humidity) while ensuring basic properties as a flame retardant material (flame retardancy, shape retention, etc.), and a resin composition that is a raw material for the foam. Furthermore, according to the present invention, it is possible to provide a foam that is capable of suppressing the progress of fire spread while ensuring flame retardancy, and a resin composition that is a raw material for the foam. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is an absorption spectrum chart of the foam of Example 1 obtained by infrared spectroscopy. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention is preferably a foam obtained by reacting a resin composition containing a resin component including an isocyanate-terminated prepolymer having at least two isocyanate groups obtained from an active hydrogen compound having two or more active hydrogens and a polyisocyanate; a polyamine; a trimerization catalyst; a flame retardant; a blowing agent; and a foam stabilizer. The viscosity of the resin component at 25°C is preferably 100 to 7,000 mPa·s. In the present specification and claims, the term "resin component" refers to an isocyanate-terminated prepolymer, and when the resin component contains polyisocyanate that has not reacted with the compound having two or more active hydrogens, this is also considered to be a resin component. In the present specification and claims, components other than these are not considered to be resin components. The foam, the method for producing the foam, the physical properties of the foam, and the uses of the foam will be described in order below.

[0012] <Foam> <Overall structure> The foam according to the present invention is preferably a closed-cell type foam, and the foam density of the foam is 10 to 200 kg / m 3 is preferably 10 to 100 kg / m 3 More preferably, it is 10 to 50 kg / m 3 It is more preferable that:

[0013] <Chemical structure> (Isocyanurate ring content (isocyanurate ratio)) The isocyanurate ratio in the foam according to the present invention is preferably 20% or more and 50% or less, and more preferably 25% or more and 50% or less. Here, the isocyanurate ratio is a value calculated by the following formula 1.

[0014] (Formula 1) Isocyanurate ratio (%) = P1 / (P1+P2+P3+P4) x 100

[0015] Here, P1 is the peak area derived from the isocyanurate structure contained in the absorption spectrum of the foam obtained by infrared spectroscopy. P2 is the peak area derived from the C=O of the urea structure contained in the absorption spectrum of the foam obtained by infrared spectroscopy. P3 is the peak area derived from the C=O of the urethane structure and the isocyanurate structure contained in the absorption spectrum of the foam obtained by infrared spectroscopy. P4 is the peak area derived from the NH contained in the urethane structure and the urea structure contained in the absorption spectrum of the foam obtained by infrared spectroscopy. More specifically, P1 is the peak area derived from the isocyanurate structure contained in the absorption spectrum of the foam obtained by infrared spectroscopy, and is the peak area at a wave number of 1410 cm. -1 P1 is the area of ​​the peak derived from the nurate ring in the vicinity. -1 P1 indicates the content of isocyanurate structures formed by the reaction of isocyanate groups derived from the raw materials. P2 is the peak area derived from C=O of the urea structure contained in the absorption spectrum of the foam obtained by infrared spectroscopy, and has a wave number of 1595 cm. -1 P2 is the area of ​​the peak due to the C=O of the nearby urea bond. -1 P2 indicates the content of urea structures formed by the reaction of isocyanate groups derived from the raw materials. P3 is the peak area derived from C=O of urethane structures and isocyanurate structures contained in the absorption spectrum of the foam obtained by infrared spectroscopy, and is in the range of wave number 1710 cm -1 P3 is the area of ​​the peak of the C=O bond in the vicinity. -1 P3 indicates the content of urethane structures and isocyanurate structures formed by the reaction of isocyanate groups derived from the raw materials. P4 is the peak area derived from NH contained in the urethane structures and urea structures contained in the absorption spectrum of the foam obtained by infrared spectroscopy, and is in the range of wave number 1510 cm. -1 P4 is the area of ​​the peak derived from the nearby NH. -1P4 indicates the content of urethane structures and urea structures contained in the foam, and indicates the content of urethane structures and urea structures formed by the reaction of isocyanate groups derived from the raw materials. Therefore, the sum of P1 to P4 indicates the total number of isocyanate groups derived from the raw materials that have reacted. Therefore, the isocyanurate conversion rate is a value indicating the proportion of isocyanurate structures among the isocyanate groups derived from the raw materials that have reacted.

[0016] <Method of manufacturing foam> <Foam raw materials> A suitable raw material for the foam according to the present invention is a resin composition containing a resin component containing an isocyanate-terminated prepolymer having at least two isocyanate groups, which is obtained from a compound having two or more active hydrogens and a polyisocyanate; a polyamine; a catalyst (including a trimerization catalyst); a flame retardant; a blowing agent; and a foam stabilizer. Note that other resin components (e.g., polyisocyanates different from the isocyanate-terminated prepolymer) or other components may also be used as the raw material. Each raw material will be described in detail below.

[0017] (Isocyanate-terminated prepolymer) The isocyanate-terminated prepolymer is a compound having at least two isocyanate groups obtained from a compound having two or more active hydrogens and a polyisocyanate. The weight-average molecular weight of the prepolymer is preferably in the range of 300 to 5000, more preferably in the range of 300 to 4000, and even more preferably in the range of 400 to 3000. The weight-average molecular weight of the prepolymer can be measured by gel permeation chromatography (GPC) (standard polymer = polystyrene). The isocyanate-terminated prepolymer can be obtained, for example, by blending an excess amount of polyisocyanate over the number of moles of the compound having two or more active hydrogens (for example, Patent 5121699, Patent 4883490).

[0018] Compounds with two or more active hydrogen atoms Here, examples of the compound having two or more active hydrogens, which is one of the raw materials of the prepolymer, include low molecular weight diols such as ethylene glycol and diethylene glycol, polyols, polyhydric phenols, polyamines, alkanolamines, polythiols, etc. The compound having two or more active hydrogens is preferably at least one selected from polyols, polyamines, and polythiols, and is preferably a polyol and / or a polyamine. The following will explain each in turn.

[0019] The polyol is not particularly limited, and examples thereof include polyester polyol, polycarbonate polyol, polyether polyol, polyester ether polyol, polyalkylene polyol, etc. Among these, polyester polyol is preferable, and polyester polyol using aliphatic dicarboxylic acid as a raw material is particularly preferable.

[0020] The polyester polyol is not particularly limited, and examples thereof include aliphatic dicarboxylic acids such as succinic acid, adipic acid, sebacic acid, and azelaic acid, aromatic dicarboxylic acids such as phthalic acid, terephthalic acid, isophthalic acid, and naphthalenedicarboxylic acid, alicyclic dicarboxylic acids such as hexahydrophthalic acid, hexahydroterephthalic acid, and hexahydroisophthalic acid, and acid esters or acid anhydrides thereof, and ethylene glycol, 1,3-propylene glycol, 1,2-propylene glycol, and the like. Examples of such polyols include polyester polyols such as polypropylene glycol obtained by a dehydration condensation reaction with lactone monomers such as ε-caprolactone, methyl valerolactone, and the like; and polylactone diols obtained by ring-opening polymerization of lactone monomers such as ε-caprolactone, methyl valerolactone, and the like. Examples of polycarbonate polyols include those obtained by reacting at least one of polyhydric alcohols such as ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, neopentyl glycol, 1,8-octanediol, 1,9-nonanediol, and diethylene glycol with diethylene carbonate, dimethyl carbonate, diethyl carbonate, and the like. Examples of polyether polyols include polyethylene glycol, polypropylene glycol, polytetramethylene ether glycol, and the like obtained by polymerizing cyclic ethers such as ethylene oxide, propylene oxide, and tetrahydrofuran, and copolyethers thereof. In addition, polyhydric alcohols such as glycerin and trimethylolethane can be used to polymerize the above-mentioned cyclic ethers to obtain polycarbonate polyols.Examples of polyester ether polyols include those obtained by dehydration condensation reaction of aliphatic dicarboxylic acids such as succinic acid, adipic acid, sebacic acid, and azelaic acid, aromatic dicarboxylic acids such as phthalic acid, terephthalic acid, isophthalic acid, and naphthalenedicarboxylic acid, alicyclic dicarboxylic acids such as hexahydrophthalic acid, hexahydroterephthalic acid, and hexahydroisophthalic acid, or acid esters or acid anhydrides thereof with glycols such as diethylene glycol or propylene oxide adducts, or mixtures thereof. Examples of polyalkylene polyols include polyalkylene glycols such as polyethylene glycol, polypropylene glycol, and polytetramethylene glycol, polybutadiene polyols, polyethylene glycol-polypropylene glycol copolymers, polyethylene glycol-polytetramethylene glycol copolymers, and polypropylene glycol-polytetramethylene glycol copolymers.

[0021] The polyhydric phenol is not particularly limited, and examples thereof include monocyclic polyhydric phenols such as pyrogallol and hydroquinone; and bisphenols such as bisphenol A, bisphenol F, and bisphenol sulfone.

[0022] The polyamine is not particularly limited, and examples thereof include aliphatic polyamines, aromatic polyamines, and alicyclic polyamines. Specific examples include 4,4-methylenebis(N-sec-butylaniline), 4,4-methylene-bis(2-methylcyclohexylamine), 4,4'-diamino-3,3'-dichlorodiphenylmethane, trimethylene-bis(4-aminobenzoate), 4,4'-diamino-3,3'-diethyl-5,5'-dimethyldiphenylmethane, polytetramethylene oxide-di-p-aminobenzoate, 2,2',6,6'-tetraethyl-4,4'-methylenedianiline, 4,4'-methylenebis(2-isopropyl-6-methylaniline), 4,4'-methylenebis(2,6-diisopropylaniline), 4,4'-methylenebis(3-chloro-2,6-diethylaniline), 3,5-diethyltoluene-2,4-diamine, and dimethylthiotoluenediamine.

[0023] The polythiol is not particularly limited, and examples thereof include bis-(2-hydrothioethyloxy)methane, dithioethylene glycol, dithioerythritol, and dithiothreitol.

[0024] The alkanolamine is not particularly limited, and examples thereof include diethanolamine, ethanolisopropanolamine, diisopropanolamine, ethanol-2-hydroxybutylamine, isopropanol-2-hydroxybutylamine, triethanolamine, N-methylaminoethanol, N-normal butyltylaminoethanol, N-tert-butylaminoethanol, N-ethylaminoethanol, N-benzylaminoethanol, and N-(2-hydroxyethyl)piperazine.

[0025] The hydroxyl value of the polyol and polyhydric phenol is preferably 50 to 1000 mgKOH / g, more preferably 80 to 850 mgKOH / g, and even more preferably 100 to 700 mgKOH / g, where the hydroxyl value is a value measured in accordance with JIS-K0070.

[0026] The mercapto value (SH value) of the polythiol is preferably 50 to 1000 mgKOH. Here, the mercapto value of the polythiol is determined by the following method. Mercapto value (SH value; mgKOH / g): A sample is weighed into a 100 mL (milliliter) sample bottle (the mass is accurately read in grams to four decimal places), and 5 mL of acetic anhydride-tetrahydrofuran solution (containing 4 g of acetic anhydride in 100 mL of solution) and 10 mL of 4-dimethylaminopyridine-tetrahydrofuran solution (containing 1 g of 4-dimethylaminopyridine in 100 mL of solution) are accurately added to completely dissolve the sample, followed by stirring at room temperature for 1 hour, and then 1 mL of ultrapure water is accurately added and stirred at room temperature for 30 minutes, followed by titration with 0.5 M potassium hydroxide-ethanol solution (indicator: phenolphthalein). The SH value was calculated by the following formula. SH value (mgKOH / g) = 28.05 × (BA) / S (In the formula, S represents the amount of sample taken (g), A represents the amount of 0.5M potassium hydroxide-ethanol solution required for titration of the sample (mL), and B represents the amount of 0.5M potassium hydroxide-ethanol solution required for the blank test (mL).)

[0027] The amine value of the polyamine is preferably 50 to 1000 mgKOH / g, and more preferably 50 to 800 mgKOH / g. The amine value of the polyamine is measured by the total amine value measurement method described in JIS K1557-7:2011 "Plastics - Test methods for polyurethane raw material polyols - Part 7: Determination of basicity (indication of nitrogen content and total amine value)".

[0028] The hydroxyl value of the alkanolamine is preferably 50 to 1000 mgKOH / g, and more preferably 50 to 800 mgKOH / g.

[0029] Two or more types of compounds having active hydrogen may be used in combination.

[0030] PolyisocyanatesThe polyisocyanate is not limited as long as it is a compound having a plurality of isocyanate groups, and may be any of aromatic, aliphatic, and alicyclic. For example, bifunctional polyisocyanates include 2,4-toluene diisocyanate (2,4-TDI), 2,6-toluene diisocyanate (2,6-TDI), m-phenylene diisocyanate, p-phenylene diisocyanate, 4,4'-diphenylmethane diisocyanate (4,4'-MDI), 2,4'-diphenylmethane diisocyanate (2,4'-MDI), 2,2'-diphenylmethane diisocyanate (2,2'-MDI), hydrogenated MDI, xylylene diisocyanate, 3,3'-dimethyl-4, Aromatic compounds such as 4'-biphenylene diisocyanate, 3,3'-dimethoxy-4,4'-biphenylene diisocyanate, polymethylene polyphenyl polyisocyanate, 1,5-naphthalene diisocyanate, xylylene diisocyanate (XDI), hydrogenated XDI, tetramethylxylene diisocyanate (TMXDI), cyclohexane-1,4-diisocyanate, isophorone diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, methylcyclohexane diisocyanate, etc. Alicyclic ones such as butane-1,4-diisocyanate, hexamethylene diisocyanate, isopropylene diisocyanate, methylene diisocyanate, lysine diisocyanate, and other alkylene-based ones; trifunctional or higher polyisocyanates include 1-methylbenzene-2,4,6-triisocyanate, 1,3,5-trimethylbenzene-2,4,6-triisocyanate, biphenyl-2,4,4'-triisocyanate, diphenylmethane-2,4,4'-triisocyanate, methyldiphenylmethane-2,4,4'-triisocyanate, and other polyisocyanates. Examples of the isocyanate include dimethyldiphenylmethane-4,6,4'-triisocyanate, 4,4'-dimethyldiphenylmethane-2,2',5,5' tetraisocyanate, triphenylmethane-4,4',4"-triisocyanate, polymeric MDI, lysine ester triisocyanate, 1,3,6-hexamethylene triisocyanate, 1,6,11-undecane triisocyanate, bicycloheptane triisocyanate, 1,8-diisocyanatomethyloctane, and the like; and may also include modified products and derivatives thereof.These polyisocyanates can be used alone or in combination. Among these, MDI, TDI, or modified or derivatives of MDI or TDI are preferred, and monomeric MDI and crude MDI are more preferred.

[0031] Other ingredients As described above, the essential raw materials for the isocyanate-terminated prepolymer according to the present invention are a compound having two or more active hydrogens and a polyisocyanate. However, as long as there are two or more isocyanate groups at the end of the prepolymer (for example, isocyanate groups at both ends of the main chain, an isocyanate group at one end of the main chain + an isocyanate group at a side chain, or an isocyanate group at multiple side chains), a polymerizable component forming a part of the skeleton of the prepolymer or a component for modifying the side chain, etc. may be used. As described above, "end" does not mean only both ends, but is a concept that it is sufficient to have two or more isocyanate groups at any point of the skeleton.

[0032] Here, the NCO% in the resin component containing the isocyanate-terminated prepolymer is preferably 10 to 35% by mass, more preferably 15 to 30% by mass, and particularly preferably 17 to 28% by mass. The NCO% (isocyanate content) of the resin component is measured in accordance with Method A (toluene / dibutylamine, hydrochloric acid method) of JIS K1603-1:2007 "Test method for aromatic isocyanates in plastics - polyurethane raw materials, Part 1: Determination of isocyanate group content".

[0033] The viscosity of the resin component containing the isocyanate-terminated prepolymer at 25° C. is preferably 100 to 7,000 mPa·s, more preferably 200 to 6,500 mPa·s, and even more preferably 350 to 5,000 mPa·s. By setting the viscosity within the above range, it is possible to achieve a good balance between properties such as residual weight and volume change rate at high temperatures and flame resistance.

[0034] (Polyamine) The polyamine is not particularly limited, and examples thereof include aliphatic polyamines, aromatic polyamines, alicyclic polyamines, etc. Specific examples thereof include 4,4-methylenebis(N-sec-butylaniline), diethyldiaminotoluene, 4,4-phenylenebis(N-sec-butylaniline), 4,4-methylenebis(N-sec-butylaniline), 4,4-methylene-bis(2-methylcyclohexylamine), 4,4'-diamino-3,3'-dichlorodiphenylmethane, trimethylene-bis(4-aminobenzoate), 4,4'-diamino-3,3'-diethyl-5,5'-dimethyldiphenylmethane, polytetramethylene Examples of suitable amines include dimethylthiotoluene, dimethylthiotoluenediamine ...

[0035] The amine value of the polyamine is preferably 50 to 1000 mgKOH / g, and more preferably 50 to 800 mgKOH / g. The amine value of the polyamine is measured by the total amine value measurement method described in JIS K1557-7:2011 "Plastics - Test methods for polyurethane raw material polyols - Part 7: Determination of basicity (indication of nitrogen content and total amine value)".

[0036] (catalyst) The catalyst includes a trimerization catalyst. Examples of the trimerization catalyst include metal oxides such as lithium oxide, sodium oxide, and potassium oxide; alkoxides such as sodium methoxy, sodium ethoxy, sodium propoxy, sodium butoxy, potassium methoxy, potassium ethoxy, potassium propoxy, and potassium butoxy; organic metal salts such as potassium acetate, potassium octylate, potassium caprylate, and iron oxalate; 2,4,6-tris(dimethylaminomethyl)phenol, N,N',N"-tris(dimethylaminopropyl)hexahydrotriazine, triethylenediamine, and the like; Examples of the tertiary amines include tertiary amines such as 1,3,5-tris(dimethylaminopropyl)hexahydro-s-triazine; derivatives of ethyleneimine; acetylacetone chelates of alkali metals, aluminum, and transition metals, quaternary ammonium salts; and nitrogen-containing heterocyclic compounds such as diazabicycloundecene (DBU). These can be used alone or in combination. Of these, it is more preferable to use organic metal salts, quaternary ammonium salts, and nitrogen-containing heterocyclic compounds. In addition, a foaming catalyst or a resinification catalyst may be included.

[0037] Examples of the foaming catalyst include tertiary amines or organic acid salts thereof such as N,N,N',N',N''-pentamethyldiethylenetriamine, bis(2-dimethylaminoethyl)ether, N,N,N',N',N''-pentamethyldipropylenetriamine, N,N-dimethylaminoethoxyethanol, N,N,N'-trimethylaminoethoxyethanol, N,N,N',N'',N''-hexamethyltriethylenetetramine, N,N,N',N''-tetramethyl-N''-(2-hydroxylethyl)triethylenediamine, and N,N,N',N''-tetramethyl-(2-hydroxylpropyl)triethylenediamine, morpholine compounds, and piperazine compounds, and one or more of these can be used.

[0038] Examples of the resinification catalyst include N,N,N',N',N''-pentamethyldiethylenetriamine, triethylenediamine (TEDA), triethylenediamine, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetramethylhexamethylenediamine, N,N,N',N'-tetramethylpropylenediamine, N,N,N',N'',N''-pentamethyl-(3-aminopropyl)ethylenediamine, N,N,N',N'',N'', Tertiary amines or organic acid salts thereof, such as '-pentamethyldipropylenetriamine, N,N,N',N'-tetramethylguanidine, 1,3,5-tris(N,N-dimethylaminopropyl)hexahydro-S-triazine, bismuth tris(2-ethylhexanoate), bismuth tris(neodecanoate), bismuth tris(palmitate), bismuth tetramethylheptanedioate, bismuth octoate, bismuth naphthenate, and dibutyltin dilaurate. organometallic compounds such as tin octoate, dibutyltin dimaleate, dibutyltin diacetate, dioctyltin diacetate, tin octoate, and dimethyltin dimercaptide; imidazoles such as titanium-(2-ethylhexoxide), 1-methylimidazole, 2-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-isopropylimidazole, and 1-isobutyl-2-methylimidazole; or N-methyl-N′-(2-dimethylimidazole). Examples of the bis(dimethylaminoethyl)piperazine include N,N'-dimethylpiperazine, N-methylpiperazine, N-methylmorpholine, N-ethylmorpholine, 1,8-diazabicyclo[5.4.0]undecene-7, 1,1'-(3-(dimethylamino)propyl)imino)bis(2-propanol), bismuth 2-ethylhexanoate, N,N-dimethylaminoethanol, and bis(dimethylaminoethyl)ether. One or more of these can be used.

[0039] (Flame retardant) As the flame retardant, red phosphorus is preferable. Furthermore, it is preferable to use at least one selected from phosphoric acid ester, phosphate-containing flame retardant, bromine-containing flame retardant, boron-containing flame retardant, antimony-containing flame retardant, and metal hydroxide in combination with red phosphorus. In addition, other flame retardants may be included. Specific examples of the phosphoric acid ester include aromatic phosphoric acid esters such as triphenyl phosphate, cresyl diphenyl phosphate, tricresyl phosphate, trixylenyl phosphate, tris(t-butylated phenyl) phosphate, tris(i-propylated phenyl) phosphate, and 2-ethylhexyl diphenyl phosphate; aromatic condensed phosphoric acid esters such as 1,3-phenylene bis(diphenyl phosphate), 1,3-phenylene bis(dixylenyl) phosphate, resorcinol bis(diphenyl) phosphate, and bisphenol A bis(diphenyl phosphate); halogen-containing phosphoric acid esters such as tris(dichloropropyl) phosphate, tris(β-chloropropyl) phosphate, and tris(chloroethyl) phosphate; and halogen-containing condensed phosphoric acid esters such as 2,2-bis(chloromethyl)trimethylene bis(bis(2-chloroethyl) phosphate) and polyoxyalkylene bisdichloroalkyl phosphate.Examples of the phosphate-containing flame retardant include monophosphates, ammonium salts such as ammonium phosphate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate; sodium salts such as monosodium phosphate, disodium phosphate, trisodium phosphate, monosodium phosphite, disodium phosphite, and sodium hypophosphite; potassium salts such as monopotassium phosphate, dipotassium phosphate, tripotassium phosphate, monopotassium phosphite, dipotassium phosphite, and potassium hypophosphite; lithium salts such as monolithium phosphate, dilithium phosphate, trilithium phosphate, monolithium phosphite, dilithium phosphite, and lithium hypophosphite; barium salts such as barium dihydrogen phosphate, barium hydrogen phosphate, tribarium phosphate, and barium hypophosphite; magnesium salts such as monohydrogen magnesium phosphate, magnesium hydrogen phosphate, trimagnesium phosphate, and magnesium hypophosphite; calcium salts such as calcium dihydrogen phosphate, calcium hydrogen phosphate, tricalcium phosphate, and calcium hypophosphite; zinc salts such as zinc phosphate, zinc phosphite, and zinc hypophosphite; and aluminum salts such as monoaluminum phosphate, dialuminum phosphate, trialuminum phosphate, aluminum phosphite, and aluminum hypophosphite. Examples of the polyphosphate include ammonium polyphosphate, piperazine polyphosphate, melamine polyphosphate, ammonium amide polyphosphate, and aluminum polyphosphate.Examples of the bromine-containing flame retardant include pentabromodiphenyl ether, octabromodiphenyl ether, decabromodiphenyl ether, tetrabromobisphenol A (TBBA), TBBA-epoxy oligomer, TBBA-polycarbonate oligomer, TBBA-bis(dibromopropyl ether), TBBA-bis(aryl ether), and other TBBA compounds; bisphenylpentamethane, 1,2-bis(2,4,6-tribromophenoxy)ethane, 2,4,6-tris(2,4,6-tribromophenoxy)-1,3,5-triazine, 2,6-dibromophenol, 2,4-dibromophenol, and other polybenzene ring compounds; brominated polystyrene, brominated styrene, and other brominated styrene compounds; phthalic acid compounds, such as ethylenebistetrabromophthalimide; and cyclic aliphatic compounds, such as hexabromocyclododecane. Examples of the boron-containing flame retardant include borax; boron oxides such as diboron trioxide, boron trioxide, diboron dioxide, tetraboron trioxide, and tetraboron pentoxide; boric acid compounds such as boric acid, lithium borate, sodium borate, potassium borate, cesium borate, magnesium borate, calcium borate, barium borate, zirconium borate, zinc borate, aluminum borate, and ammonium borate. Examples of the boron-containing flame retardant include antimony oxides such as antimony trioxide and antimony pentoxide; antimonate salts such as sodium antimonate and potassium antimonate; pyroantimonate salts such as sodium pyroantimonate and potassium pyroantimonate; and the like. These can be used alone or in combination. Examples of metal hydroxides include aluminum hydroxide and magnesium hydroxide. Other flame retardants can be used as known flame retardants. Other flame retardants include, for example, chlorine compounds such as chlorinated paraffin; nitrogen compounds such as hindered amines and melamine cyanurate; cellulose; and the like.

[0040] (foaming agent) Examples of the foaming agent include water, hydrocarbons (preferably C4 to C6), hydrofluoroolefins, and carbon dioxide gas. Specifically, examples include cyclopentane, HFO (1336mzz), and HFO (1233zd). These may be used alone or in combination. The foaming agent may or may not contain water. However, when at least one of the foaming agents is water, the amount is preferably 2 parts by mass or less, more preferably 1 part by mass or less, and particularly preferably 0.75 parts by mass or less, relative to 100 parts by mass of the resin component.

[0041] (Foam stabilizer) Examples of the foam stabilizer include silicone compounds such as polyalkylsiloxane-polyoxyethylene-polyoxypropylene graft copolymers and polyalkylsiloxane-polyoxyethylene-polyoxypropylene linear block copolymers; nonionic surfactants such as fluorine-based hydrocarbon compounds, acrylic-polyoxyalkylene copolymers, polyoxyethylene-polyoxypropylene copolymers, acetylene diol compounds, polyoxyethylene fatty acid esters, polyoxyethylene alkyl ethers, polyoxyethylene phenyl ethers, polyoxyethylene phenyl ethers, polyoxyethylene alkyl phenyl ethers, glycerin fatty acid esters, sorbitan fatty acid esters, and sucrose fatty acid esters. These can be used alone or in combination.

[0042] (Other Ingredients) The resin composition according to the present invention may further contain other components in addition to the above components. In particular, it is preferable to contain a polyisocyanate. The polyisocyanate is not limited as long as it is a compound having a plurality of isocyanate groups, and may be any of aromatic, aliphatic, and alicyclic. For example, the polyisocyanate described above as a raw material for producing an isocyanate-terminated prepolymer can be exemplified. In particular, MDI, or a modified or derivative of MDI is preferable, and monomeric MDI is more preferable. In addition, as other components, known additives such as antioxidants, ultraviolet absorbers, antibacterial agents, tackifiers, and compatibilizers can be added.

[0043] When polyisocyanate is further contained, the prepolymer / isocyanate ratio (mass ratio) is preferably 20 / 80 to 95 / 5, more preferably 30 / 70 to 70 / 30, and particularly preferably 40 / 60 to 67.5 / 27.5.

[0044] The resin composition can be prepared, for example, by adding and mixing each component. In this case, when preparing a resin composition further containing polyisocyanate and / or polyamine in addition to the prepolymer as the resin component, (1) a method of adding polyisocyanate and / or polyamine separately from the prepolymer or (2) a method of adding polyisocyanate and / or polyamine in an amount exceeding the equivalent ratio during preparation of the prepolymer, resulting in the presence of unreacted polyisocyanate and / or polyamine, may be used.

[0045] ·Isocyanate Index The isocyanate index of the above-mentioned resin composition is preferably 150 to 800, more preferably 200 to 600, and further preferably 200 to 500. Here, the isocyanate index refers to a value obtained by multiplying the ratio of the number of moles of all active hydrogens in the resin composition to the number of moles of isocyanate groups in the polyisocyanate by 100 (number of moles of NCO / number of moles of active hydrogen × 100).

[0046] <Method of manufacturing foam> The foam of the present invention can be produced, for example, by mixing an isocyanate-terminated prepolymer, a polyamine, a catalyst, a blowing agent, a foam stabilizer, and a flame retardant in advance to prepare a resin composition, which is then foamed and cured. Known methods can be used for mixing the resin composition and for foaming and curing. When used in a spraying method, a mixture in which a raw material not having an isocyanate group is mixed in advance and a raw material having an isocyanate group can be mixed in a spraying device immediately before application of the foam.

[0047] The amount of the isocyanate-terminated prepolymer is preferably 1 to 100 mass %, more preferably 10 to 100 mass %, even more preferably 10 to 90 mass %, and particularly preferably 20 to 80 mass %, based on the total mass of the resin components.

[0048] The amount of polyisocyanate added is preferably 1 to 80% by mass based on the total mass of the resin components.

[0049] The amount of polyamine blended is preferably 0.1 to 30 mass %, more preferably 0.1 to 28 mass %, even more preferably 0.1 to 15 mass %, and particularly preferably 0.1 to 10 mass %, based on the total mass of the resin components.

[0050] The amount of the foam stabilizer to be added may be preferably 0 to 10 parts by mass with respect to 100 parts by mass of the resin component.

[0051] The amount of the trimerization catalyst is, for example, 0.1 parts by mass or more and 15 parts by mass or less, preferably 1 part by mass or more and 10 parts by mass or less, more preferably 1.5 parts by mass or more and 8.0 parts by mass or less, and even more preferably 1.8 parts by mass or more and 6.0 parts by mass or less, relative to 100 parts by mass of the resin component.

[0052] The amount of the resinification catalyst is 0 to 15 parts by mass, preferably 0.1 to 10.0 parts by mass, and more preferably 0.2 to 7.0 parts by mass, per 100 parts by mass of the resin component.

[0053] The amount of the foaming catalyst to be added is preferably 0 to 5 parts by mass with respect to 100 parts by mass of the resin component.

[0054] The amount of red phosphorus to be added is preferably 0 to 30 parts by mass, and more preferably 2 to 20 parts by mass, relative to 100 parts by mass of the resin component.

[0055] The blending amount of the flame retardant other than red phosphorus is preferably 0 to 50 parts by mass, and more preferably 10 to 40 parts by mass, based on 100 parts by mass of the resin component.

[0056] <Physical properties of foam> <Remaining weight> The remaining weight (600°C) of the foam according to the present invention is preferably 30% by weight or more, more preferably 35% by weight or more, and even more preferably 40% by weight or more. The value of the remaining weight is a value measured according to the method described in the Examples. Similarly, the remaining weight (held at 300°C for 30 minutes) of the foam according to the present invention is preferably 60% by weight or more, more preferably 70% by weight or more, and even more preferably 80% by weight or more. The value of the remaining weight is a value measured according to the method described in the Examples. When the remaining weight is in the above range, the collapse of the flame retardant material at high temperatures is suppressed, making it possible to suppress the spread of fire.

[0057] <Volume change rate> The foam tends to expand easily at high temperatures (e.g., 300°C) and to shrink easily when exposed to higher temperatures (e.g., 400°C). If the volume change rate from expansion to contraction is small, the spread of fire due to deformation of the adherend is suppressed. Therefore, the volume change rate of the foam according to the present invention is preferably less than 120% (300°C) based on the original volume, more preferably less than 100% (300°C), and even more preferably less than 80% (300°C). In addition, the difference between the volume change rate at 300°C and the volume change rate at 400°C of the foam according to the present invention is preferably within 150%, more preferably within 100%, and even more preferably within 80%. In addition, when exposed to higher temperatures (e.g., 500°C), the residue at high temperatures becomes an important parameter, so how much remains after heating becomes an important factor. From this viewpoint, the volume change rate of the foam according to the present invention is preferably within ±50% (500° C.) of the original volume, more preferably within ±40% (500° C.), and even more preferably within ±30% (500° C.) The volume change rate value is a value measured according to the method described in the examples.

[0058] <Limit oxygen index> The limiting oxygen index of the foam according to the present invention is preferably 27% or more, more preferably 29% or more, and even more preferably 32% or more. The upper limit is not limited, but is, for example, 35. The limiting oxygen index is a value measured according to the method described in the examples.

[0059] <Flame retardancy> The foam of the present invention has a radiant heat intensity of 50 kW / m2 according to the ISO-5660 test method. 2 The total heat generated after 20 minutes was 25 MJ / m 2 can be less than 8.5MJ / m 2 The following is preferred:

[0060] <Change in compressive strength> The foam according to the present invention preferably has a compressive strength change rate (%) before and after moist heat treatment (80°C x RH85% x 1 month) of 20% or more and 50% or less, and more preferably less than 20%.

[0061] <Uses of foam> The foam of the present invention is used for architectural applications (walls, ceilings, roofs, floors, etc.), fittings (windows, shoji screens, sliding doors, sliding doors, transoms, etc.), ships and storage tanks for transporting oil and gas, vehicles (engines, batteries, ceilings, floors, door panels, etc.), aircraft, transport aircraft, cold storage bags for transporting medicines, freezers and refrigerators, plant facilities, and electrical appliances such as refrigerators, heat retaining walls, insulation materials, and cold resistance mitigation materials, underground filling reinforcement materials in land subsidence prevention works and road construction, injection repair materials for civil engineering applications such as tunnels, bridges, and floating piers, structural filling materials for unnecessary basements, energy absorbing materials, waterproofing materials, water stopping materials, buoyancy materials, etc. In addition, in wooden or reinforced concrete buildings, etc., since insulation construction is easy, it can be used as a foam for spraying construction methods.

[0062] The above-mentioned resin composition may be divided into two or more components. When the resin composition is divided into two or more components, the components are divided so that the curing reaction does not start when each component of the resin composition is divided into two or more components, but starts after the components are mixed.

[0063] Another aspect of the present invention is a system that is a combination or reaction system for forming a resin composition that includes a first liquid (base resin) containing a resin component including an isocyanate-terminated prepolymer, a second liquid (curing agent) containing a polyamine and a trimerization catalyst, a flame retardant, a blowing agent, and a foam stabilizer.

[0064] The flame retardant, blowing agent, and foam stabilizer may be contained in the first or second liquid, or may be provided separately from the first and second liquids. Preferably, the trimerization catalyst, flame retardant, blowing agent, and foam stabilizer are contained in the second liquid. The system for forming the resin composition is provided as an apparatus including a first container for containing the first liquid and a second container for containing the second liquid, such as a caulking gun or a spray container. EXAMPLES

[0065] <<Preparation of resin composition>> <Raw materials> (Prepolymer) Polyol A-1: ​​Phthalate ester polyol (p-phthalic acid / diethylene glycol) (OHV=250, functional group number: 2) Polyol A-2: Phthalate ester polyol (p-phthalic acid / diethylene glycol + tetraethylene glycol) (OHV=200, functional group number: 2) Polyol A-3: Aliphatic modified phthalate ester polyol (adipic acid + p-phthalic acid / diethylene glycol) (OHV=250, functional group number: 2) Polyol A-4: Polypropylene glycol (OHV=240, functional group number: 3) Polyol A-5: Polybutadiene polyol (OHV=77, functional group number: 2) Polyol A-6: Adipic acid ester polyol (adipic acid / diethylene glycol) (OHV=112, functional group number: 2) Polyamine B-1: 4,4-methylenebis(N-sec-butylaniline) (amine value: 526) Polyisocyanate I-1: Monomeric MDI (NCO%: 33.5%) Polyisocyanate I-2: Crude MDI (NCO%: 31.4%) Polyisocyanate I-3: TM-50 (monomeric MDI / TDI=50:50 mixture, NCO: 39.5%) (Polyisocyanate) Polyisocyanate I-2: Crude MDI (NCO%: 31.4%) (Polyamine) Polyamine B-1: 4,4-methylenebis(N-sec-butylaniline) (amine value: 526) Polyamine B-2: Diethyldiaminotoluene (amine value: 486) Polyamine B-3: 4,4-phenylenebis(N-sec-butylaniline) (amine value: 637) Polyamine B-4: Aniline-terminated PTMG (amine value: 250) (trimerization catalyst) CT-1: 1,3,5-tris(dimethylaminopropyl)hexahydro-s-triazine CT-2: Diazabicycloundecene (DBU) ·CT-3: Quaternary ammonium salt (tetraalkylammonium acetate salt) ·CT-4: Potassium acetate ·CT-5: Quaternary ammonium salt (2-ethylhexanoic acid tetraalkylammonium salt) (Resinification catalyst) CP-1: Dimethyltin dimercaptide (Sn-based catalyst) CP-2: Triethylenediamine CP-3: Bis(dimethylaminoethyl) ether CP-4: 1,2-Dimethylimidazole CP-5: N,N-Dimethylaminoethanol CP-6: Pentamethyldiethylenetriamine CP-7: Bismuth 2-ethylhexanoate (Bi-based catalyst) CP-8: Titanium tetra(2-ethylhexoxide) (Ti-based catalyst) (Flame retardant) FL-1: Red phosphorus FL-2: TCPP (halogen-containing phosphate ester) FL-3: PFR (phosphate ester) FL-4: Ammonium polyphosphate (phosphate) FL-5: Poly(pentabromophenyl acrylate) (bromine-based) FL-6: Zinc borate (boron type) FL-7: Antimony trioxide (antimony type) FL-8: Aluminum hydroxide (metal hydroxide) (foaming agent) ·FA-1: Hydrofluoroolefin FA-2: Water (Foam stabilizer) ·FS-1: Silicone surfactant

[0066] <Preparation of prepolymer> A 5L polyethylene container equipped with a mechanical stirrer, an anchor-type stirring blade, and a nitrogen inlet tube was charged with a predetermined amount of polyisocyanate shown in Tables 1 to 12 at 25°C, and the liquid temperature of the isocyanate was set to 25°C. A predetermined amount of polyol or polyamine shown in Tables 1 to 12 was added stepwise to the container so that the liquid temperature did not exceed 80°C. After the addition of the polyol or polyamine was completely completed, the mixture was stirred at a stirring speed of 60 rpm for 2 hours to react the above isocyanate with the polyol or polyamine, thereby obtaining an isocyanate-terminated prepolymer. The NCO group content of the resin component containing the obtained prepolymer was measured in accordance with JIS K1603-1 (Method A), and it was confirmed that the NCO group content was the predetermined value. In addition, the viscosity (mPa·s) of the resin component containing the isocyanate-terminated prepolymer at 25°C was measured in accordance with JIS K 7117-2.

[0067] <Preparation of Resin Composition> In a 500 mL polypropylene disposable cup, polyamine, trimerization catalyst, flame retardant, blowing agent, foam stabilizer, and other additives were weighed out in the amounts shown in Tables 1 to 12 for each Example and Comparative Example, and used as the mixed liquid for each Example and Comparative Example. Each mixed liquid was stirred and mixed at 2000 rpm for 5 minutes using a stirrer equipped with a propeller-type stirring blade, to obtain the first composition for each Example and Comparative Example. The first composition obtained and the second composition (prepolymer and polyisocyanate in some cases) in the amounts shown in Tables 1 to 12 were placed in a 10°C cooling furnace and cooled to 10±1°C separately. The first composition and the second composition for each Example and Comparative Example were stirred and mixed at 2000 rpm for 5 seconds using a stirrer equipped with a propeller-type stirring blade, foamed, and cured, to obtain the foam for each Example and Comparative Example.

[0068] <<Evaluation>> <Isocyanate Index (INDEX)> The isocyanate index (INDEX) was calculated for the first composition and the second composition of each of the Examples and Comparative Examples. The results are shown in Tables 1 to 12. <Measurement of isocyanurate ratio> The foams of each Example and Comparative Example 24 hours after foaming were subjected to infrared absorption spectrum measurement using a Fourier transform infrared spectrometer (FT-IR, JASCO Corporation, Model FT / IR-4200). The measurement was performed by the ATR method using a diamond prism, and the measurement was performed 50 times. The isocyanurate group content in the foam was calculated from formula (1). The measurement was performed at three points in the foam rise direction, the top, the center, and the bottom, and the average value was shown. The results are shown in Tables 1 to 12.

[0069] <Measurement of residual weight (600℃)> 3 to 5 mg was taken from the center of the foam of each Example and Comparative Example 24 hours after foaming, and the sample was filled in an aluminum pan. The weight loss behavior of the sample was observed in the temperature range of 25°C to 600°C using a TG / DTA measuring device (Model TG / DTA7200, manufactured by SII Corporation), and the remaining amount (%) of the sample was calculated from the remaining weight of the sample at 600°C. The measurement was performed at a temperature rise rate of 10°C / min under a dry air flow (flow rate: 250 mm / min). The results are shown in Tables 1 to 12.

[0070] <Residual weight (held at 300℃ for 30 minutes)> The method of sampling and the amount of sample were the same as in <Measurement of residual weight (600°C)>. The temperature was raised from 25°C to 300°C at a rate of 20°C / min, and the sample was heated and held at 300°C for 30 minutes to determine the residual weight.

[0071] <Measurement of limiting oxygen index> After 24 hours had passed since foaming, the skin layer was removed from the foam of each Example and Comparative Example, and 10 samples measuring 1 cm in width, 15 cm in length, and 1 cm in thickness were cut out. The samples were fixed in a glass tube with a jig and stood vertically in a candle combustion tester (Toyo Seiki Seisakusho). Then, based on JIS K7201-2, the upper end of the sample was ignited with a gas burner, and the minimum oxygen concentration required for combustion (critical oxygen index) was calculated from the ignition time and the flame spread distance.

[0072] <Total heat generation (50kW x 20 minutes) measurement> After 24 hours had passed since foaming, samples were cut out from the center of the foams of each Example and Comparative Example, measuring 10 cm in length, 10 cm in width, and 5 cm in thickness. Cone calorimeter tests were carried out on the foams in accordance with ISO5660 (Building Standards Act No. 2) to measure the total heat generation and maximum heat generation rate of the samples. The measurements were carried out at a radiant heat quantity of 50 kW / m 2 The heating time was 20 minutes. The results are shown in Tables 1 to 12.

[0073] <Volume change rate (300℃, 400℃, 500℃)> A sample (unheated sample) was cut out from the center of the foam of each Example and Comparative Example 24 hours after foaming to a length of 5 cm, width of 5 cm, and thickness of 2.5 cm, and left to stand for 5 minutes in an electric furnace heated to 300 ° C. to measure the volume change rate. The volume of the unheated sample was set to 100%, the volume after heating at 300 ° C. was measured, and the value obtained by subtracting the volume of the unheated sample from the volume after heating at 300 ° C. was divided by the volume of the unheated sample and multiplied by 100 to obtain the volume change rate at 300 ° C. Similarly, the unheated sample was left to stand for 5 minutes in an electric furnace heated to 400 ° C. to measure the volume change rate. The volume of the unheated sample was set to 100%, the volume after heating at 400 ° C. was measured, and the value obtained by subtracting the volume of the unheated sample from the volume after heating at 400 ° C. was divided by the volume of the unheated sample and multiplied by 100 to obtain the volume change rate at 400 ° C. Furthermore, the unheated sample was left to stand for 5 minutes in an electric furnace heated to 500°C. The volume of the unheated sample was set as 100%, and the volume after heating to 500°C was measured. The volume after heating to 500°C was subtracted from the volume of the unheated sample, the result was divided by the volume of the unheated sample, and multiplied by 100 to obtain the volume change rate at 500°C. If the sample expanded, a positive value is shown, and if the sample contracted, a negative value is shown. The results are shown in Tables 1 to 12.

[0074] <Change in compressive strength> The skin layer was removed from the foam 24 hours after foaming, and a test piece was cut out to a size of 10 cm long, 10 cm wide, and 5 cm thick. The test piece was then left to stand in a hot and humid heat oven at 80°C and 85% relative humidity for one month to cure. For the test pieces before and after the hot and humid heat treatment, two flat plates measuring 15 cm long, 15 cm wide, and 1 cm thick were attached to a material testing machine (AG-10, Shimadzu Corporation) based on JIS K7220, and the test piece was sandwiched between the flat plates. The test piece was compressed in this state to measure the compressive strength. Three samples were used for each test, and the average value was taken as the compressive strength, and the rate of change in the compressive strength of the foam before and after the hot and humid heat treatment was calculated.

[0075] <Flame resistance> When the foam according to the present invention is subjected to the flame contact test described in the examples, it is preferable that no cracks occur in the cross section. Further, the thickness of the carbonized layer is preferably 25 mm or less, more preferably 15 mm or less, still more preferably 8 mm or less, and particularly preferably 7.5 mm or less. When having such flame resistance, the collapse of the flame retardant material at high temperature is suppressed, and as a result, the spread of flame can be suppressed.

[0076] <Density> The apparent density of the foams of each example and comparative example after 24 hours from foaming was measured by the method described in JIS K7222:2005 "Foamed Plastics and Rubbers - Method for Determining Apparent Density". The results are shown in Tables 1 to 12.

[0077] ≪Judgment Criteria≫ ■Foaming Profile Evaluated by rise time (RT) RT ≦ 30 seconds: 4 points 30 seconds < RT ≦ 60 seconds: 2 points 60 seconds < RT ≦ 100 seconds: 0 points RT ≧ 100 seconds: -1 point ■Isocyanuration Rate 35 or more: 3 points 30 or more and less than 35: 2 points 25 or more and less than 30: 1 point Less than 25: 0 points ■Total Heat Release Less than 7: 3 points 7 to 10: 2 points Greater than 10 and 16 or less: 1 point Greater than 16 or unmeasurable: 0 points ■Residual Weight (1) 600 °C 50 or more: 5 points 40 or more and less than 50: 4 points 32 or more and less than 40: 3 points 22 or more and less than 32: 2 points 10 or more and less than 22: 1 point Less than 10: 0 points (2) Held at 300 °C for 30 minutes 80% or more: 3 points 70% to under 80%: 2 points 60% to less than 70%: 1 point Less than 60%: 0 points ■ Volume change rate 300℃ Less than 100%: 1 point 100% or more: 0 points 400℃ Difference from 300℃ is within 100%: 1 point Difference from 300℃ is more than 100%: 0 points 500℃ Within ±30%: 1 point Above +30% and below -30%: 0 points ■ Rate of change in compressive strength Less than 10%: Yes (2 points) 10% to less than 20%: △ (1 point) 20% or more: × (0 points) ■ Presence or absence of cross-sectional cracks 〇: 2 points ×: 0 points Pierce: -1 point ■ Depth of carbonized layer 4mm or less: 3 points Above 4mm and below 10mm: 2 points Above 10mm and below 30mm: 1 point Above 30mm: 0 points <Overall Judgment> Total points ◎: 18 points or more 〇: 16~17 points △: 14~15 points ×: 13 points or less

[0078] [Table 1]

[0079] [Table 2]

[0080] [Table 3]

[0081]

Table 4

[0082]

Table 5

[0083]

Table 6

[0084]

Table 7

[0085]

Table 8

[0086]

Table 9

[0087]

Table 10

[0088]

Table 11

[0089]

Table 12

Claims

1. The composition comprises: a resin component including an isocyanate-terminated prepolymer having at least two isocyanate groups, the prepolymer being obtained by reacting a compound having two or more active hydrogens with a polyisocyanate; a polyamine; a trimerization catalyst; a flame retardant; a foaming agent; and a foam stabilizer; The polyamine is at least one selected from the group consisting of aromatic polyamines selected from aliphatic polyamines, alicyclic polyamines, 4,4-methylene bis(N-sec-butylaniline), 4,4-methylene-bis(2-methylcyclohexylamine), 4,4'-diamino-3,3'-dichlorodiphenylmethane, trimethylene-bis(4-aminobenzoate), 4,4'-diamino-3,3'-diethyl-5,5'-dimethyldiphenylmethane, polytetramethylene oxide-di-p-aminobenzoate, 2,2',6,6'-tetraethyl-4,4'-methylene dianiline, 4,4'-methylene bis(2-isopropyl-6-methylaniline), 4,4'-methylene bis(2,6-diisopropylaniline), 4,4'-methylene bis(3-chloro-2,6-diethylaniline), and dimethylthiotoluenediamine; A resin composition, characterized in that the NCO% in the resin component is 10 to 35 mass%.

2. The composition comprises: a resin component including an isocyanate-terminated prepolymer having at least two isocyanate groups, the prepolymer being obtained by reacting a compound having two or more active hydrogens with a polyisocyanate; a polyamine; a trimerization catalyst; a flame retardant; a foaming agent; and a foam stabilizer; the compound having two or more active hydrogens is one or more selected from the group consisting of polyhydric phenols, polyamines, polythiols, polyester polyols, polycarbonate polyols, and polyester ether polyols; A resin composition, characterized in that the NCO% in the resin component is 10 to 35 mass%.

3. 3. The resin composition according to claim 1, wherein the viscosity of the resin component at 25° C. is 100 to 7,000 mPa·s.

4. The resin composition according to any one of claims 1 to 3, wherein the trimerization catalyst is an organometallic salt, a quaternary ammonium salt, or a nitrogen-containing heterocyclic compound.

5. The resin composition according to any one of claims 1 to 4, wherein the resin composition contains red phosphorus as the flame retardant.

6. The resin composition according to claim 5, further comprising at least one flame retardant selected from the group consisting of phosphoric esters, phosphate-containing flame retardants, bromine-containing flame retardants, boron-containing flame retardants, antimony-containing flame retardants, and metal hydroxides.

7. A foam obtained from the resin composition according to any one of claims 1 to 6.

8. The foam according to claim 7, wherein the isocyanurate ratio in the foam is 20% or more and 50% or less.

9. A foam obtained from a resin composition comprising: a resin component containing an isocyanate-terminated prepolymer having at least two isocyanate groups, the prepolymer being obtained by reacting a compound having two or more active hydrogens with a polyisocyanate; a polyamine; a trimerization catalyst; a flame retardant; a blowing agent; and a foam stabilizer, The foam has an isocyanurate ratio of 20% or more and 50% or less.

10. A foam obtained from a resin composition comprising: a resin component containing an isocyanate-terminated prepolymer having at least two isocyanate groups, the prepolymer being obtained by reacting a compound having two or more active hydrogens with a polyisocyanate; a polyamine; a trimerization catalyst; a flame retardant; a foaming agent; and a foam stabilizer, The density of the foam is 200 kg / m 3 is as follows: A foam, wherein the resin component has an NCO% of 10 to 35 mass%.

Citation Information

Patent Citations

  • Hollow light transmission plate main body and hollow light transmission plate using the same

    JP1995005326A

  • Polyisocyanate composition, method for preparing the same and method for producing rigid polyurethane foam

    JP2005213306A

  • Rigid polyurethane foam composition

    JP2013023510A

  • Method for producing polyurethane resin

    JP2013072083A

  • Method for producing polyurethane resin

    JP2014125623A